2015
DOI: 10.1371/journal.pone.0129452
|View full text |Cite
|
Sign up to set email alerts
|

Methylated Host Cell Gene Promoters and Human Papillomavirus Type 16 and 18 Predicting Cervical Lesions and Cancer

Abstract: Change in the host and/or human papillomavirus (HPV) DNA methylation profile is probably one of the main factors responsible for the malignant progression of cervical lesions to cancer. To investigate those changes we studied 173 cervical samples with different grades of cervical lesion, from normal to cervical cancer. The methylation status of nine cellular gene promoters, CCNA1, CDH1, C13ORF18, DAPK1, HIC1, RARβ2, hTERT1, hTERT2 and TWIST1, was investigated by Methylation Specific Polymerase Chain Reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…[ 9 ] Promoter methylation of C13ORF18 leads to disruption of cell cycle and seems to be an early event in cervical cancerogenesis. [ 10 ] In this study, no relationship was found between MGMT and C13ORF18 expression and DNA methylation. Either promoter hypermethylation or histone deacetylation could inactivate or deregulate MGMT and C13ORF18 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[ 9 ] Promoter methylation of C13ORF18 leads to disruption of cell cycle and seems to be an early event in cervical cancerogenesis. [ 10 ] In this study, no relationship was found between MGMT and C13ORF18 expression and DNA methylation. Either promoter hypermethylation or histone deacetylation could inactivate or deregulate MGMT and C13ORF18 .…”
Section: Discussionmentioning
confidence: 53%
“…[ 9 ] A study on methylation status of nine gene promoters revealed that methylation biomarkers distinguishing cervical precursor lesions from normal cervix were primarily C13ORF18 . [ 10 ] This study was designed to verify the efficacy of MGMT and C13ORF18 methylation and HR-HPV for the triage of cytology screening samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, hypermethylation of the TERT promoter was found to be significant in CIN3 lesions [107] and cervical cancer samples [108]. TERT promoter variants c.-146C > T and c.-124C > T were observed in 21.4% of cervical cancer patients in India, which is almost 4 times higher than the proportions reported by studies in Western populations [109].…”
Section: Senescence and Apoptosis Evasion Pathwaysmentioning
confidence: 73%
“…The other two studies were conducted in 2010 and 2015. Both studies found that normal tissue also had RAR β promoter methylation, which made it a poor predictor of progression to severe disease[ 62 , 64 ]. However, one of the two studies also investigated the level of methylation using quantitative methylation-specific PCR and found that although normal cells were methylated, the level of methylation increased in LSIL, HSIL, and invasive cancer tissue[ 62 ].…”
Section: Epigenetic Mechanisms and Risk Of Cancer Developmentmentioning
confidence: 99%